2020
DOI: 10.1016/j.semradonc.2019.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte-Sparing Radiotherapy: The Rationale for Protecting Lymphocyte-rich Organs When Combining Radiotherapy With Immunotherapy

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 85 publications
(120 reference statements)
0
39
0
Order By: Relevance
“…The main physical advantages are the sparing of the lymphocytes, essential cells to set off an immune response against the metastatic cancer cells. In fact, sparing lymph nodes is now being proposed as a standard practice also for conventional radiotherapy [59]. In addition, cell-death pathways induced by heavy ions seem to be more immunogenic than for X-rays, resulting in enhanced biological effectiveness [60,61].…”
Section: Combined Treatmentsmentioning
confidence: 99%
“…The main physical advantages are the sparing of the lymphocytes, essential cells to set off an immune response against the metastatic cancer cells. In fact, sparing lymph nodes is now being proposed as a standard practice also for conventional radiotherapy [59]. In addition, cell-death pathways induced by heavy ions seem to be more immunogenic than for X-rays, resulting in enhanced biological effectiveness [60,61].…”
Section: Combined Treatmentsmentioning
confidence: 99%
“… 87 Therefore, of late, blood is seen as a moving OAR, and lymphocyte-sparing RT has been advocated to mitigate treatment-related lymphopenia. 88 Lymphocyte-sparing RT aims to deliver a dose as low as reasonably achievable to lymphocyte-rich regions, including large blood vessels, the heart, and lymphoid organs. 88 Irradiating with PT, hypofractionation, or radio-surgery in the setting of patients with NSCLC reduced lymphopenia, which is a prognostic indicator in patients receiving immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“… 88 Lymphocyte-sparing RT aims to deliver a dose as low as reasonably achievable to lymphocyte-rich regions, including large blood vessels, the heart, and lymphoid organs. 88 Irradiating with PT, hypofractionation, or radio-surgery in the setting of patients with NSCLC reduced lymphopenia, which is a prognostic indicator in patients receiving immunotherapy. 89 Among patients with esophageal cancer treated with definitive chemoradiation, a retrospective analysis indicated that PT reduced the risk of sustained grade 4 lymphopenia compared with IMRT, 90 and a reduction in integral dose reduced grade 4 lymphopenia with PT.…”
Section: Introductionmentioning
confidence: 99%
“…Although BM represents only part of the pelvic reservoir lymphoid organs together with lymph nodes, circulating lymphocytes, and gut mucosa, radiation-induced BM suppression is a predictor of leukopenia and lymphopenia (6,7,20,21). BM stem cells are exquisitely radiosensitive and, in the average adult population, half of the hematopoietically active BM (aBM) is located within pelvic bones and lumbar vertebrae (6,7,20,21).…”
mentioning
confidence: 99%
“…Proton therapy offers dosimetric advantages in BM sparing when delivering PNRT as compared to intensity-modulated radiotherapy and volumetric arc therapy (32,33). Therefore, stereotactic body radiotherapy (SBRT) and proton therapy may represent promising approaches for "lymphocyte sparing radiotherapy" (21,31). Additionally, brachytherapy, given the favorable dose distribution to normal tissues, should also be kept in mind for more effective "immune-sparing" radiotherapy approaches (34)(35)(36)(37).…”
mentioning
confidence: 99%